2018
DOI: 10.1002/cbic.201800434
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Assembled Dipeptide Nanoparticles with Adjustable Fluorescence Emission for Multicolor Bioimaging

Abstract: Peptide self-assembly, inspired by the naturally occurring fabrication principle, remains the most attractive in constructing fluorescent nanoagents towards bioimaging. However, the noncovalent interactions that drive peptide self-assembly are usually susceptible to the complex physiological environment; thus leading to disassembly and dysfunction of fluorescent nanoagents. Herein, a covalently crosslinked assembly strategy for fabrication of stable peptide-based nanoparticles with adjustable emission is intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Cytotoxicity and cell imaging studies demonstrated an excellent stability of the resultant CDP NPs, even after intracellular uptake, allowing them to be used for sustainable in vivo multicolor fluorescent imaging. [ 153 ]…”
Section: Biomedical Applications Of Peptide‐engineered Fluorescent Nanomaterialsmentioning
confidence: 99%
“…Cytotoxicity and cell imaging studies demonstrated an excellent stability of the resultant CDP NPs, even after intracellular uptake, allowing them to be used for sustainable in vivo multicolor fluorescent imaging. [ 153 ]…”
Section: Biomedical Applications Of Peptide‐engineered Fluorescent Nanomaterialsmentioning
confidence: 99%
“…Because of the chemical diversity of peptides, they are exploited as adjustment factors in constructing supramolecular nanodrugs . A number of peptide‐modulated nanodrugs are used for antitumor therapy . Phototherapy involves two main factors: light and phototherapeutic agents.…”
Section: Supramolecular Nanodrugs Based On Self‐assembling Peptidesmentioning
confidence: 99%
“…However, these approaches usually produce redundant structures as a single peptide chain is used to fold into a fluorescent nanostructure, which restricts the conformation and functionality of the labeled target. Recently, dipeptides have been found to selfassemble into fluorescent nanostructures, such as the phenylalanine–phenylalanine (FF) dipeptide, whose emission can be modulated by both the morphology and size of the assembled structures as well as by covalent cross‐linking . Some inorganic ions such as Zn 2+ can also coassemble with tryptophan‐containing peptides such as the phenylalanine–tryptophan (FW) and cyclic tryptophan–tryptophan (cWW) dipeptides .…”
Section: Figurementioning
confidence: 99%